Marketing Strategy of Sari Delicatessen Pastry Shop at Sari Pacific Jakarta - Marya Yenny; Reni Sulistyowati; Maryetti; Milanda Afriani (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: This research aims to discover a marketing strategy that could improve pastry products at Sari Delicatessen Sari Pacific Jakarta. Research methods: The data collection method used was purposive sampling. This research is descriptive qualitative using SWOT analysis to evaluate and identify opportunities, maximize strength, decrease weakness and avoid threats. Results and discussion: The S-O, S-T, W-O, and W-T strategies implemented to improve pastry products at Sari Delicatessen Sari Pacific Jakarta are creating more variated products, expanding market segments, creating new products for home delivery, and also developing facilities to accommodate the customer’s needs. The score for internal factors of Sari Delicatessen Sari Pacific Jakarta is 3.65, and the external factor score is 3.55. Thus, it can be concluded that the business position matrix in the IFAS and EFAS is in quadrant 1 or has a solid competitive position and fast market growth. Implication: The pastry products at Sari Delicatessen at Hotel Sari Pacific Jakarta need to maintain factors that fall into the category of opportunities so that marketing strategies through the optimal promotion are expected to increase sellers of pastry products at Sari Delicatessen. Keywords: hotel, pastry shop, marketing strategy, SWOT analysis.